Welcome to Westonci.ca, the Q&A platform where your questions are met with detailed answers from experienced experts. Discover solutions to your questions from experienced professionals across multiple fields on our comprehensive Q&A platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
To find the perimeter of the triangle whose vertices are [tex]\((2, -3)\)[/tex], [tex]\((-7, 0)\)[/tex], and [tex]\((-3, -4)\)[/tex], we need to calculate the lengths of each side of the triangle and then sum these lengths.
### Step 1: Calculate the Length of Each Side
The distance between two points [tex]\((x_1, y_1)\)[/tex] and [tex]\((x_2, y_2)\)[/tex] can be calculated using the distance formula:
[tex]\[ d = \sqrt{(x_2 - x_1)^2 + (y_2 - y_1)^2} \][/tex]
#### Side 1: Between [tex]\((2, -3)\)[/tex] and [tex]\((-7, 0)\)[/tex]
Use the distance formula:
[tex]\[ \text{Side 1} = \sqrt{((-7) - 2)^2 + (0 - (-3))^2} = \sqrt{(-9)^2 + 3^2} = \sqrt{81 + 9} = \sqrt{90} = 3\sqrt{10} \][/tex]
#### Side 2: Between [tex]\((-7, 0)\)[/tex] and [tex]\((-3, -4)\)[/tex]
Use the distance formula:
[tex]\[ \text{Side 2} = \sqrt{((-3) - (-7))^2 + ((-4) - 0)^2} = \sqrt{(4)^2 + (-4)^2} = \sqrt{16 + 16} = \sqrt{32} = 4\sqrt{2} \][/tex]
#### Side 3: Between [tex]\((-3, -4)\)[/tex] and [tex]\((2, -3)\)[/tex]
Use the distance formula:
[tex]\[ \text{Side 3} = \sqrt{(2 - (-3))^2 + (-3 - (-4))^2} = \sqrt{(5)^2 + 1^2} = \sqrt{25 + 1} = \sqrt{26} \][/tex]
### Step 2: Calculate the Perimeter
The perimeter [tex]\(P\)[/tex] of the triangle is the sum of the lengths of its sides:
[tex]\[ P = \text{Side 1} + \text{Side 2} + \text{Side 3} \][/tex]
Substituting the calculated lengths:
[tex]\[ P = 3\sqrt{10} + 4\sqrt{2} + \sqrt{26} \][/tex]
The exact perimeter of the triangle is:
[tex]\[ 3\sqrt{10} + 4\sqrt{2} + \sqrt{26} \][/tex]
So the perimeter of the triangle is:
[tex]\[ 20.242706743590304 \][/tex]
This includes all steps and shows how to use the distance formula to find the lengths and sum them to find the perimeter.
### Step 1: Calculate the Length of Each Side
The distance between two points [tex]\((x_1, y_1)\)[/tex] and [tex]\((x_2, y_2)\)[/tex] can be calculated using the distance formula:
[tex]\[ d = \sqrt{(x_2 - x_1)^2 + (y_2 - y_1)^2} \][/tex]
#### Side 1: Between [tex]\((2, -3)\)[/tex] and [tex]\((-7, 0)\)[/tex]
Use the distance formula:
[tex]\[ \text{Side 1} = \sqrt{((-7) - 2)^2 + (0 - (-3))^2} = \sqrt{(-9)^2 + 3^2} = \sqrt{81 + 9} = \sqrt{90} = 3\sqrt{10} \][/tex]
#### Side 2: Between [tex]\((-7, 0)\)[/tex] and [tex]\((-3, -4)\)[/tex]
Use the distance formula:
[tex]\[ \text{Side 2} = \sqrt{((-3) - (-7))^2 + ((-4) - 0)^2} = \sqrt{(4)^2 + (-4)^2} = \sqrt{16 + 16} = \sqrt{32} = 4\sqrt{2} \][/tex]
#### Side 3: Between [tex]\((-3, -4)\)[/tex] and [tex]\((2, -3)\)[/tex]
Use the distance formula:
[tex]\[ \text{Side 3} = \sqrt{(2 - (-3))^2 + (-3 - (-4))^2} = \sqrt{(5)^2 + 1^2} = \sqrt{25 + 1} = \sqrt{26} \][/tex]
### Step 2: Calculate the Perimeter
The perimeter [tex]\(P\)[/tex] of the triangle is the sum of the lengths of its sides:
[tex]\[ P = \text{Side 1} + \text{Side 2} + \text{Side 3} \][/tex]
Substituting the calculated lengths:
[tex]\[ P = 3\sqrt{10} + 4\sqrt{2} + \sqrt{26} \][/tex]
The exact perimeter of the triangle is:
[tex]\[ 3\sqrt{10} + 4\sqrt{2} + \sqrt{26} \][/tex]
So the perimeter of the triangle is:
[tex]\[ 20.242706743590304 \][/tex]
This includes all steps and shows how to use the distance formula to find the lengths and sum them to find the perimeter.
Thanks for stopping by. We are committed to providing the best answers for all your questions. See you again soon. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.